Indicadores de sustentabilidade em três propriedades de cafeicultura familiar em Araponga MG: uma análise descritiva - Souza, Luiza Monteiro (2014)
The present dissertation analyses the production systems and the environmental, economic and sociopolitical sustainability of properties of familybased coffee production with different levels of use of agroecological management in the agroecosystem and in the participation in social organizations in the municipality of Araponga, State of Minas Gerais, Brazil. The present research aimed to evaluate the sustainability of properties of familybased coffee production, and to compare the sustainability of properties in transition to an agroecological management, inserted or not, in the local organizations of the municipality of Araponga. The methodology was performed in four steps: a) selection of the families; b) characterization of the properties by two tools of the Participatory Rural Appraisal, the semi-structured interview and the crossway walk; c) data collection in the coffee crops; and d) Selection of the sustainability indicators for the sociopolitical, economic and environmental dimensions. The research was performed in three families small farmers with coffee production. In total it was selected 62 indicators: 18 sociopolitical, 13 economics, and 23 environmental for the coffee crops; and 8 environmental indicators for the property as a whole. The indicators were measured and translated in a single scale to support de comparison between them. It was established three values of sustainability: 1 critical level; 2 acceptable level; 3 desired level. The results were plotted in a spider chart, in order to facilitate the interpretation of the indicators. The property A obtained better Global Sustainability Index compared with the other assessed properties. In addition, property A showed best indices in the sociopolitical, economic and environmental dimensions of the coffee crops. At the other side, property C was the one with the worst Global Sustainability Index and also the worst indices of the three sustainability dimensions. The property B obtained medium values indices, except for the property s environmental sustainability index, which obtained the best position.